2012
DOI: 10.1055/s-0031-1301320
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Tactical Behaviour in Football

Abstract: The present study explored how football players' dynamic positional data can be used to assess tactical behaviour by measuring movement patterns and inter-player coordination. A pre post-test design was used to assess the effects of a 13-week constructivist and cognitivist training program by measuring behaviour in a 5 × 5 football small-sided game, played on a 60 × 40 m outdoor natural turf pitch. Data was captured at 5 Hz by GPS devices (SPI Pro, GPSports, Canberra, Australia) and analysed with non-linear si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
147
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(159 citation statements)
references
References 11 publications
1
147
0
11
Order By: Relevance
“…In addition, the literature anales de psicología, 2017, vol. 33, nº 3 (october) describes several useful frameworks for studying intra-and inter-team behavior and dynamics in SSGs (Folgado, Lemmink, Frencken, & Sampaio, 2014;Sampaio & Maçãs, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the literature anales de psicología, 2017, vol. 33, nº 3 (october) describes several useful frameworks for studying intra-and inter-team behavior and dynamics in SSGs (Folgado, Lemmink, Frencken, & Sampaio, 2014;Sampaio & Maçãs, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with an ecological dynamics approach (Seifert, Button, & Davids, 2013), use of the same task constraints in training sessions involving players with different levels of expertise could lead to the emergence of different tactical behaviors (Silva et al, 2014 a, b & c). More skilled players tend to form a larger team shape, which could be interpreted as a strategy for creating space (Sampaio & Maçãs, 2012;Silva et al, 2014b). Folgado et al (2014), using player length per width ratio measurements, showed how the shape of teams varied in different SSGs according to player age and numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Probablemente, por un lado, a nivel individual, un peor componente neuromuscular y capacidad anaeróbica (Harley et al 2010) en los sub13 podría influir en una menor eficiencia de carrera y, por tanto en un mayor player load. Por otro lado, a nivel colectivo, una mayor alternancia en la posesión del balón en jugadores sub13 menos expertos (Folgado, Lemmink, Frencken, & Sampaio, 2014) podría ser la causa de que los jugadores se vieran obligados a alternar continuamente las labores ofensivas y defensivas, provocando un mayor número de cambios de dirección, una mayor carrera no lineal o un juego más desordenado (Sampaio & Maçãs, 2012), lo que podría favorecer un aumento de aceleraciones, desaceleraciones y cambio de dirección. Recientemente se ha comenzado a proponer ratios entre la distancia total de carrera y el PL como métrica para valorar la eficiencia de la carrera o tipología de la tarea (Polglaze, Dawson, Hiscock, & Peeling, 2015), por poner algunos ejemplos.…”
Section: Discussionunclassified
“…As in other team sports, the success relies on cooperative relationships between players of the same team and their behaviour towards the opponent team [11][12][13], which together are known as idiosyncratic intra-and inter-dynamic interactions [14]. Previous studies have reported the importance of environmental and situational variables, such as the type of competition [13], match location (home vs. away) [4,15], match status [16,17], elapsed match time/game period [5,18], and psychological goal [19].…”
Section: Introductionmentioning
confidence: 99%
“…These factors influence both attacking and defensive behaviours [20]. Accordingly, match analysis based on behavioural tactics appears to be the most effective for studying the dynamic patterns of the game [14]. With this in mind, a number of studies have adopted the observational methodology from psychological research, in particular the sequential and diachronic type of analysis [11,12,21,22].…”
Section: Introductionmentioning
confidence: 99%